2021
DOI: 10.1097/anc.0000000000000891
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Moral Distress and Intent to Leave a Position Among Neonatal Intensive Care Nurses

Abstract: Background: The phenomenon of moral distress is prevalent in the literature, but little is known about the experiences of nurses working in the neonatal intensive care unit (NICU). In addition, a paucity of literature exists exploring the relationship between moral distress and intent to leave a position in NICU nurses. Purpose: To explore the phenomenon of moral distress in NICU nurses using the Measure of Moral Distress for Health Care Professionals (MMD-HP) survey. Methods: A cross-sectional, descriptive, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
(99 reference statements)
1
6
0
Order By: Relevance
“…In a systematic review by YektaKooshali et al, the intensity and frequency of moral distress among nurses were reported to be moderate in 2018 ( 12 ). Hally et al concluded that the NICU nurses who scored high in measure of moral distress for health care professionals are more likely to leave their work ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review by YektaKooshali et al, the intensity and frequency of moral distress among nurses were reported to be moderate in 2018 ( 12 ). Hally et al concluded that the NICU nurses who scored high in measure of moral distress for health care professionals are more likely to leave their work ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding moral distress is important due to the significant impact, it has on burnout and staff turnover, as well as uncertainty about clinical outcomes. 3,8,9,[20][21][22][23][24][25][26] We found that moral distress levels were moderately correlated with burnout, as well as weakly correlated with uncertainty about the benefit of treatment. These correlations are similar to those found in studies in pediatric critical care units and indicate a similar level of unease in our unit.…”
Section: Discussionmentioning
confidence: 60%
“…Understanding moral distress is important due to the significant impact, it has on burnout and staff turnover, as well as uncertainty about clinical outcomes 3,8,9,20–26 . We found that moral distress levels were moderately correlated with burnout, as well as weakly correlated with uncertainty about the benefit of treatment.…”
Section: Discussionmentioning
confidence: 71%
“…Understanding moral distress is important due to the significant impact it has on burnout and staff turnover (3,(8)(9)(20)(21)(22)(23)(24)(25)(26). In addition, burnout is associated with poorer quality of care, and significant expenses due to decreased clinical productivity and early retirement (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%